Social entrepreneurship in the interface between public communication and social capital - Oliveira, Maria José da Costa; Nader, Silvana Maria (Organicom, 2017)
This article, which is based on socio-psychological theory and critical theory, addresses the social entrepreneurship from the perspective of public communication and social capital. The purpose is to analyze how the correlation between those concepts can present an option for social development, since, in the context of democracy, a conception of development cannot be tied only to the logic of the market that privileges the private gains to the detriment of the public interest. The notion of a social entrepreneur becomes relevant by the perspective of the feasibility of actions aimed at the sustainability of the third sector and other perspectives of social action, which, although using management processes, oppose the view of competition with the view of cooperation; it values social capital rather than evidencing the economic capital; it creates a new meaning for the capitalist logic to a more human side, in which the economic topic serves the social development.